Cultivation techniques and medicinal properties of pleurotus spp - Gregori, Andrej (Array, 2007)
The genus Pleurotus (oyster mushroom) comprises some most popular edible mushrooms due to their favourable organoleptic and medicinal properties, vigorous growth and undemanding cultivation conditions. It can be cultivated on log and a wide variety of agroforestry (by-)products, weeds and wastes for the production of food, feed, enzymes and medicinal compounds, or for waste degradation and detoxification. Many different techniques and substrates have been successfully utilized for mushroom cultivation and biomass production by means of solid-state and submerged liquid fermentation. However, in contrast to submerged liquid fermentation, solid-state fermentation is not often used in large scale due to severe engineering problems. Various Pleurotus species have been shown to possess a number of medicinal properties, such as antitumour, immunomodulatory, antigenotoxic, antioxidant, anti-inflammatory, hypocholesterolaemic, antihypertensive, antiplatelet-aggregating, antihyperglycaemic, antimicrobial and antiviral activities. These therapeutic activities are exhibited by extracts or isolated compounds from Pleurotus spp. fermentation broth, mycelia and fruiting bodies. In particular, polysaccharides appear to be potent antitumour and immuno-enhancing substances, besides possessing other beneficial activities. However, the biochemical mechanisms of these therapeutic activities still remain largely unknown. This review focuses on recent advances in the biotechnology of Pleurotus spp., with emphasis on the production of fruiting bodies, the production of mycelium and bioactive compounds by solid-state and submerged liquid fermentation. The medicinal properties of this mushroom are also outlined